In need of a cultural shift to promote restorative justice in Southern Europe. Issue 4 (1st October 2016) - Bussu, A.
Abstract: The article describes the main results of a European project on restorative justice (RJ) called Freedom Wings (FW) and presents a new model to promote RJ in Southern Europe, which was developed from FW findings. The principal mission of the FW project is to disseminate best practices of RJ within a transnational network and to promote community participation in conflict prevention and resolution, in order to support individual and social well-being. This paper presents the main findings of multiagency and professional focus groups exploring restorative approaches and community justice. Observation of experts' social representation of RJ helped the authors to understand the operation of the justice systems in each country and the attitudes of senior officials towards implementing restorative practices in a way that actively involves the community. The analysis shows the necessity of a cultural change in order to switch from a form of RJ managed by the judicial system to one led by the community . The EU project enabled the research team to theorize a model for promoting a relational and restorative community.